EFFECT OF HYDROLYSABLE TANNIN SUPPLEMENTATION ON PRODUCTION PERFORMANCE OF DAIRY CROSSBRED COWS - M. Ali; H. A. Mehboob; M. A. Mirza; H. Raza; M. Osredkar (Journal of Animal and Plant Sciences, 2017)
Nowadays, hydrolysable tannin has been introduced to improve the protein utilization in ruminants. The objective of this study was to determine the effect of hydrolysable tannin on production performance (milk production and composition) of dairy crossbred cows. In this experiment, 12 crossbred lactating cows (average milk production 10 liters/day) were used in this experiment. The cows were randomly divided into four groups (A, B, C and D). In group A, animals were fed basal diet without supplementation of hydrolysable tannin, however; the animals in groups B, C and D fed basal diet with 20, 30 and 40 g hydrolysable tannin per day, respectively. Duration of the study was 55 days including 10 days of adaptation period. Milk yield was daily (morning and evening) recorded during the experimental period. For milk composition analyses, the milk sample was collected fortnightly from each cow. Milk samples were analyzed for milk protein, fat, lactose, total solids and milk urea contents. Results showed that the milk production was found significantly higher (P<0.05) in group D. The differences in milk fat and total solids were non-significant (P>0.05) between groups. However, the milk protein and lactose (%) were increased with supplementation of hydrolysable tannin. There was reduction in milk urea content of animals fed diet with hydrolysable tannin supplementation but highest drop was observed in group B. The supplementation of hydrolysable tannin also results in the reduction of somatic cell count. From results of this study, it is concluded that hydrolysable tannin supplementation improves milk production and udder health.
Keywords: Hydrolysable tannin; dairy cows; milk yield; milk composition; somatic cell count